sTREM-1, MR-Pro-Adrenomedullin, clinical biochemistry and hematology in calves with neonatal sepsis - Sezer, M; Gökce, G (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to determine the changes in biochemical and hematological parameters and the expression of soluble triggering receptor expressed on myeloid cells-1 (sTREM 1) and mid-regional-pro-adrenomedullin (MR-Pro-ADM) on myeloid cells during treatment in calves with neonatal sepsis. The study group comprised 21 calves, aged 1–16 days, that fit the sepsis criteria. The control group comprised 10 healthy calves of the same age. The clinical examinations of the calves in the study group were performed at certain hours before the treatment (hour 0) and during the treatment (12th, 24th, 48th, and 72nd hours). The blood samples were taken from the vena jugularis before and during treatment from the sick calves and once from the healthy calves. The sTREM-1 levels before treatment (0 h), during treatment (12th, 24th, 48th, and 72nd hours) and control group was follows 59.17±2.58 ng/L, 57.07±1.65 ng/L, 57.27±2.07 ng/L, 56.64±1.97 ng/L, 57.58±2.18 ng/L and 75.60±2.57 ng/L,39 respectively. The MR-Pro-ADM levels before treatment (0 h), during treatment (12th, 24th, 48th, and 72nd hours) and control group was follows; 117.88±7.75 ng/L, 113.63±5.18 ng/L, 109.97±5.25 ng/L, 114.50±5.35 ng/L, 111,84±5.63 ng/L,65.31±2.81 ng/L, respectively. The serum MR-Pro-ADM levels in calves with sepsis were significantly higher than those in the control group before and during treatment (P < 0.05). Also, the serum sTREM-1 level was significantly lower before and after treatment in the sepsis group compared with the control group (P < 0.05). MR-Pro-ADM and sTREM-1 were more important, especially in terms of diagnosis in evaluating calves with neonatal sepsis.